Gradient-enhanced damage model for large deformations of elastic-plastic materials (Archives of Mechanics - Test, 2013)
This paper deals with the development of a family of gradient-enhanced elasticity-damage-plasticity models for the simulation of failure in metallic and composite materials. The model incorporates finite deformations and is developed with the assumption of isotropy and isothermal conditions. The gradient enhancement applied to the damage part of the model aims at removing pathological sensitivity to the finite element discretization which can occur due to material softening. The attention is focused on the algorithmic aspects and on the implementation of the model using AceGen tool. The numerical verification tests of the described model are performed using the Mathematica-based package AceFEM. Particularly, uniaxial tension test for a bar with a variable cross-section and tension of a perforated plate are examined.